2011
DOI: 10.1007/s10008-011-1458-9
|View full text |Cite
|
Sign up to set email alerts
|

Surface properties of sensors based on aminophenol-polymerized film

Abstract: In this work, carbon electrodes modified with aminophenols were developed for the production of pesticides biosensors based on acetylcholinesterase. The polymers were potentiodynamically deposited on a graphite electrode surface by the oxidation of monomers, 2-aminophenol, 3-aminophenol and 4-aminophenol. The electrochemical behaviour and surface analysis of the electrodes modified by polyaminophenols non-immobilized and immobilized on acetylcholinesterase were studied by cyclic voltammetry, electrochemical im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…Our research group has reported modifications of electrode surfaces with functionalized polymers, derived from aminophenols [ 28 31 ], tyramine [ 32 ], hydroxybenzoic acid [ 33 ], hidroxyphenylacetic acid [ 34 ] and methoxyphenethylamine [ 27 ], as well as application of the modified electrodes in the immobilization and detection of biomolecules [ 35 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our research group has reported modifications of electrode surfaces with functionalized polymers, derived from aminophenols [ 28 31 ], tyramine [ 32 ], hydroxybenzoic acid [ 33 ], hidroxyphenylacetic acid [ 34 ] and methoxyphenethylamine [ 27 ], as well as application of the modified electrodes in the immobilization and detection of biomolecules [ 35 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Electropolymerized coverages are widely studied modifiers of the electrode surface to date. Among various types of monomers, amino groups containing compounds (amino acids [ 27 , 28 , 29 , 30 ], aminophenols [ 31 , 32 , 33 , 34 ], aminobenzoic acids [ 35 , 36 , 37 ]) have been shown as effective modifiers of the electrode surface that provide significant improvement of the organic analytes response. Electrodes modified with MWCNTs and oxidized MWCNTs functionalized with 4-aminophenyl phosphonic acid [ 38 ] and aminobenzene acids [ 39 ] have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Os principais métodos de imobilização são: adsorção física, ligação covalente, imobilização por aprisionamento e imobilização por ligação cruzada 28 . Eletrodos modificados eletroquimicamente com filmes poliméricos que apresentam várias funções orgânicas, como por exemplo, poliaminofenóis 43,44 , poli(ácido hidroxifenilacético) 45 , politiramina 46,47 , poli(ácido hidroxibenzóico) 48 e poli(ácido fenilacético) 49 , possibilitam o uso de filmes catiônicos e aniônicos para a incorporação de biomoléculas e desenvolvimento de biossensores 43…”
Section: Técnicas De Imobilizaçãounclassified